Flow-induced Flutter Derivatives of Bridge Decks - B. Su; Y. Liu; M. Chambalile; G. Wang; M. M. Alam; E. Barati (Journal of Applied Fluid Mechanics)
This paper presents two-dimensional numerical simulations of the self-excited forces on two bridge decks: a streamlined one (Great Belt Bridge) and a bluff one (Sunshine Skyway Bridge). It employs forced vibration simulations using the Open-source code OpenFOAM for flutter derivative identifications. A wide sensitivity study is conducted on the effects of turbulence model, Reynolds number, vibration amplitude, and wind attack angle on flutter derivative identifications. The key findings are as follows. (i) k-ε model shows its superiority in simulating self-excited forces on a bluff bridge deck, while SST k-ω exhibits advantages in the case of a streamlined bridge deck. (ii) Compared with a streamlined bridge deck, flutter derivatives of a bluff bridge deck are more sensitive to the Reynolds number due to the generation of more vortices resulting from flow separation. Both the generation and convection of the vortices are largely affected by the Reynolds number. (iii) Flutter derivatives of the bridge decks can be considered as constants if the vertical amplitude ratio and torsional amplitude are lower than 0.025 and 2°, respectively. Increasing vibration amplitude may result in remarkable variations of some flutter derivatives. (iv) The angle of attack changes the flutter derivatives by affecting the wind pressure distribution on the bridge surface. Its impact on a bluff bridge deck is larger than on a streamlined bridge deck. Besides presenting a detailed study of identifying flutter derivatives using OpenFOAM, this research provides valuable references for setting reasonable values of the investigated factors for identifying flutter derivatives of bluff and streamlined bridge decks.